Pengaruh Product Knowledge dan Online Customer Review terhadap Keputusan Pembelian Produk Hanasui pada Marketplace Shopee (Studi pada Pelanggan Hanasui di Kelurahan Tanjung Rejo Medan) - Caroline Zane K; Indawati Lestari (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstract This research aims to determine "The Influence of Product Knowledge and Online Customer Reviews on Purchase Decisions for Hanasui Products at the Shopee Marketplace (Study of Hanasui Customers in Tanjung Rejo Village, Medan)". Product knowledge is consumer knowledge related to knowledge about the characteristics or even character of the product, the consequences of using the product and the value of the level of satisfaction achieved by the product. Online Customer Reviews are a form of word of mouth communication in online sales, and potential consumers can receive information about products from other consumers. Purchasing decisions are the final decisions made by individuals and households who purchase goods and services to meet personal needs. This type of research is quantitative research with an associative approach. The population used in this research was the community in Tanjung Rejo Village, Medan, with a sample size of 99 respondents. The sampling technique in this research used purposive sampling, namely a sampling technique by taking certain considerations and the data collection technique was carried out by distributing questionnaires via Google Form. Based on the results of the t test, it was found that each independent variable, Product Knowledge (X1) and Online Customer Review (X2), had a positive and significant effect on Purchasing Decisions (Y). Based on the results of the F test, it was found that Product Knowledge and Online Customer Review simultaneously had a positive and significant effect on Purchasing Decisions. In the results of the coefficient of determination test (R^2), it was found that the Adjust R Square value was 0.647 or the equivalent of a percentage of 64.7%, while the remaining 35.3% was influenced by other factors not examined in this research. Keywords: Product Knowledge, Online Customer Reviews, Purchasing Decisions